Perancangan sistem informasi persediaan barang inventaris proyek berbasis web - Sadarman Telaumbanua; Tommy Defisa; Asih Septia Rini (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
PT. Pradata Integra Media is a Leading Project Management Infrastructure Information Technology Company. With focused services for Data Center planning, Consulting, Design, Engineering, and Maintenance of Computer and Server Rooms. For incoming and outgoing goods or material systems in the Logistics division, this occurs when a project is running. The process of the incoming and outgoing goods system still uses bookkeeping or conventional techniques in processing the data and the resulting information is inaccurate so that the search for goods data takes a long time because the data is allowed to accumulate. Making web-based inventory application with PHP programming language and MySQL database at PT. Pradata Integra Media includes master data processing which consists of stock and project inventory that focuses on input of new goods, process of goods out, input of project inventory data, inventory status of goods, the process of submitting project equipment procurement, the process of making a letter of introduction for outgoing goods, inventory inventory reports and project inventory inventory reports. By using a web-based application system, it is hoped that divisions related to material goods can carry out the data collection process easily, because the speed and data collection process is more accurate, efficient and neat, making it easy to find the desired computer data.